No Student Should Be an Island: A Peer-Approach to Decoding and Disrupting - Schmöckel, Sabrina; Scharlau, Ingrid (Transformative Dialogues: Teaching and Learning Journal)
his article describes a new student-based approach to Decoding and Disrupting. This approach consists of an educational programme that works with a multidisciplinary group of undergraduate students, so-called Culture Fellows. In the programme, the students learn about theories on disciplinary cultures and their practices, Decoding the Disciplines, and communication. The programme focuses on the implicitness of disciplinary practices and how to explore them, i.e., it seeks to address the importance of making disciplinary practices, norms, and values more accessible to students. Within the programme, the Culture Fellows use a student-based variant of the Decoding the Disciplines Paradigm that we call ‘Culture Quest’. The Culture Quest supplies students with the tools to question, explore, and decode their respective disciplines and practices. Disciplinary practices often remain implicit because lecturers, with their wealth of experience and expertise in their discipline, may be operationally blind and thus no longer aware of the fact that certain practices might need to be explained. This lack of explanation or explicitness can lead to students feeling bewildered, confused or puzzled. The Culture Fellows and in particular the Culture Quest can encourage dialogue about and exploration of disciplinary cultures and their practices and can thus allow students to grasp the implicit cultural norms and expectations within their respective disciplines more clearly. The Culture Fellows and the Culture Quest provide students – and maybe even lecturers – with opportunities to engage with and reflect on teaching and learning strategies and practices.

Nachwuchs-Café: Symposium zur interdisziplinären Vernetzung von Doktorand/ innen und Postdocs - Rumlich, Dominik; Matz, Frauke (Grenzen, Grenzräume, Entgrenzungen)

Reliabilität - Rumlich, Dominik (Leistungsmessung, Evaluation und Feedback im Fremdsprachenunterricht)

Lernen in Bewegung: Warum Aktivität für Motivation und Schulerfolg entscheidend ist - Satzinger, Nicole

Hör mal, wer da spricht – Eine dialogische Perspektive auf studentische Äußerungen zu Fachkulturen - Schmöckel, Sabrina (die hochschullehre)

Qualifikationen für Bewegung, Spiel und Sport im Ganztag an Grundschulen. Einblicke in Schulen in Nordrhein-Westfalen und Niedersachsen - Noetzel, Ida; Fögen, Yvonne; Satzinger, Nicole; Miriam, Kehne (sportunterricht)

Possible Fashion Images: Operative Ekphrasis and the Reduction of Fashion Through Multimodal AI - Brachtendorf, Charlotte (Image: The Interdisciplinary Journal of Image Sciences)
With the rise of multimodal AI tools, such as DALL-E, Midjourney, or Stable Diffusion, it has never been easier and faster to produce compelling fashion images. While the proliferation of AI-generated fashion images can be seen as the ultimate triumph of the fashion image over both fashion text and fashionable garments, this paper critically examines how these images are produced, what exactly they show, and ultimately, how this impacts our understanding of fashion. Building on current research on multimodal AI, specifically text-to-image models, I argue that AI-generated fashion images are produced through textual means, that is, through “operative ekphrasis” (Bajohr 2024: 83). This means that the generation of fashion images created via multimodal AI is based on textual prompts that extract statistically probable images from a latent space, which, in turn, is the result of previously indexed and labeled image-text pairs. Because the indexing of images requires a reduction of complexity, images generated through multimodal AI are often generic. In the case of fashion images, this is reflected in the lack of texture and the reproduction of fashion photography’s conventions. As fashion photography is not necessarily a representation of ‘the world’ or even fashionable garments, it resembles AI-generated images more than other photographic genres. AI-generated fashion images are then not images of fashionable garments, but images about fashion images—a statistically probable permutation of fashion photographs from the past (cf. Meyer 2023: 108). As such, AI-generated fashion images are not only the product of a mediated collective imaginary but also feed back into it. The view on fashion shaped by AI-generated fashion images is then based on reduction and stylized normativity.

Ressourceneffiziente Fertigung von Leichtbaustrukturen - Weck, Daniel; Müller-Pabel, Michael; Krampitz, Thomas; Hecker, Christine; Selvaggio, Alessandro; Gilich, Julian; Gude, Maik; Lieberwirth, Holger; Tekkaya, A. Erman; Meschut, Gerson (Werkstattstechnik online)
Zur Steigerung der Ressourceneffizienz technischer Komponenten sind neben dem Leichtbau insbesondere neuartige Fertigungstechnologien und Prozessketten mit geschlossenen Stoffkreisläufen von großer Bedeutung. Im Beitrag werden am Beispiel einer Demonstratorstruktur aus hybriden Leichtbauprofilen (Aluminium und faserverstärktes Polyamid) technisch-technologische Lösungsoptionen für die gesamte Prozesskette inklusive des Recyclings vorgestellt und in Pilotversuchen bewertet.

An Empirical Examination of the Evaluative AI Framework - Kornowicz, Jaroslaw (International Journal of Human–Computer Interaction)

Hausdorffness of certain nilpotent cohomology spaces - Januszewski, Fabian; Sun, Binyong; Ying, Hao (Journal of Functional Analysis)
Let $(π,V)$ be a smooth representation of a compact Lie group $G$ on a quasi-complete locally convex complex topological vector space. We show that the Lie algebra cohomology space $H ^\bullet(\mathfrak{u}, V)$ and the Lie algebra homology space $H_\bullet(\mathfrak{u}, V)$ are both Hausdorff, where $\mathfrak{u}$ is the nilpotent radical of a parabolic subalgebra of the complexified Lie algebra $\mathfrak{g}$ of $G$.

Rational quiver representations: tame and wild - Januszewski, Fabian (arXiv:2510.00924)
We study representation finite $K$-rational quivers over fields of characteristic $0$ and their indecomposable representations, exploiting that all Brauer obstructions for descent of representations are trivial in this case. Contrasting the tame case, we give an example of a simple quiver of wild representation type, where we realize every possible Brauer obstruction of a given Galois extension $L/K$ in the category of quiver representations over $L$.

"One-sided, prejudiced view of Germans": Das Ressentiment als literarischer Ausdruck jüdischer Antiversöhnlichkeit bei Olga Grjasnowa und Dana Vowinckel - Spener, Anna Maria (Rückkehr des Ressentiments? Stereotype in Medien, Kulturphilosophie und Literatur (Sonderheft der Zeitschrift für deutsche Philologie))

Algorithmische Kulturen des Pflanzensammelns? Das Beispiel der Computerisierung des Botanischen Gartens und Botanischen Museums Berlin - Alpsancar, Suzana (Algorithmische Wissenskulturen. Der Einfluss des Computers auf die Wissenschaftsentwicklung)

Healthy Distrust in AI systems - Paaßen, Benjamin; Alpsancar, Suzana; Matzner, Tobias; Scharlau, Ingrid (arXiv)
nder the slogan of trustworthy AI, much of contemporary AI research is focused on designing AI systems and usage practices that inspire human trust and, thus, enhance adoption of AI systems. However, a person affected by an AI system may not be convinced by AI system design alone---neither should they, if the AI system is embedded in a social context that gives good reason to believe that it is used in tension with a person’s interest. In such cases, distrust in the system may be justified and necessary to build meaningful trust in the first place. We propose the term healthy distrust to describe such a justified, careful stance towards certain AI usage practices. We investigate prior notions of trust and distrust in computer science, sociology, history, psychology, and philosophy, outline a remaining gap that healthy distrust might fill and conceptualize healthy distrust as a crucial part for AI usage that respects human autonomy.

From Explaining to Diagnosing: A Justice-Oriented Framework of Explainable AI for Bias Detection - Fahimi, Miriam; State, Laura; Kasirzadeh, Atoosa (Proceedings of the AAAI/ACM Conference on AI, Ethics, and Society)
Explainable AI (XAI) methods can support the identification of biases in automated decision-making (ADM) systems. However, existing research does not sufficiently address whether these biases originate from the ADM system or mirror underlying societal inequalities. This distinction is important because it has major implications for how to act upon an explanation: while the societal bias produced by the ADM system can be algorithmically fixed, societal inequalities demand societal actions. To address this gap, we propose the RR-XAI-framework (recognition-redistribution through XAI) that builds on a distinction between socio-technical and societal bias and Nancy Fraser's justice theory of recognition and redistribution. In our framework, explanations can play two distinct roles: as a socio-technical diagnosis when they reveal biases produced by the ADM system itself, or as a societal diagnosis when they expose biases that reflect broader societal inequalities. We then outline the operationalization of the framework and discuss its applicability for cases in algorithmic hiring and credit scoring. Based on our findings, we argue that the diagnostic functions of XAI are contingent on the provision of such explanations, the resources of the audiences, as well as the current limits of XAI techniques.

Standardising Equality in the Algorithmic Society? A Research Agenda - Xenidis, Raphaële; Fahimi, Miriam (Proceedings of Fourth European Workshop on Algorithmic Fairness)
In 2024, the EU adopted the AI Act, a new set of rules for trustworthy artificial intelligence. This legal instrument carves a large place for standardisation, a regulatory technique that consists in crafting so-called harmonised technical standards, to facilitate legal compliance by industry stakeholders. While EU technical standards have been used in the past for ensuring product safety, for the first time the AI Act relies on standardisation to facilitate compliance with fundamental rights, including the right to non-discrimination and equality. The attempt to translate inherently open-textured rights and ethical principles into operationalizable standards raises critical questions. In particular, how will standardisation practices under the new EU AI Act affect, transform, contest and stabilise notions of equality and non-discrimination in an increasingly algorithmic society? This paper proposes a research agenda to address this question and unpack the black box of AI standardisation.

L'islam dans la culture populaire: Reconfigurations et nouvelles visiblités
La France contemporaine révèle un large éventail d’expressions d’une conscience(franco-)musulmane plurielle et visible. Cet ouvrage se penche sur ces nouvelles visibilités de l’islam dans la culture populaire et accorde une importance particulière au protagonisme des femmes musulmanes ainsi qu’à la culture populaire dans l’espace numérique. Il démontre également que la quête d’une nouvelle visibilité est à la fois un moteur d’intégration et de productivité culturelle, mais aussi génératrice de conflits.

Hugo De Schepper: 'A latere principis u de su theniente general'. De regeringsraden naast landsheren en landvoogden in de Habsburgse Nederlanden: Leden, instellingen en algemene politiek, 1577/1580-1609, Leuven: Peeters 2023 - Huybrechts, Yves (Sehepunkte)

Szenarien digitaler Lehre: online, blended, hybrid und inverted - Neiske, Iris; Spannagel, Christian (Praxishandbuch Hochschullehre II)

Static Light Scattering for Lignin Particle Size Characterization - Makkonen, Janita; Ahvenainen, Patrik; Bertella, Stefania; Kellock, Miriam; Saha, Sanjib; Huber, Klaus; Farooq, Muhammad; Österberg, Monika; Penttilä, Paavo (Particle & Particle Systems Characterization)
Abstract Lignin, a widely available and renewable organic polymer, has several desirable properties and applications. However, as a by‐product of pulp and paper industry, it is mainly burned for energy. Limited understanding of the complex and heterogeneous structure and a shortage of tailored analysis methods hinder its utilization in higher value applications. This study describes and compares the use of two different static light scattering methods, laser diffraction and small‐angle light scattering (SALS), for studying lignin particle size in suspension. The results from laser diffraction showed that the selected particle concentration and absorption coefficient affect the measured sizes especially for particles <1 µm in diameter. For irregularly shaped particles with broad size distributions, sampling is the most important parameter affecting the results. SALS proved an efficient method for obtaining information on particle aggregation by providing primary particle sizes as well as aggregate sizes. Characterization of samples with spherical particles and narrow size distributions is straightforward with both laser diffraction and SALS, whereas the interpretation of results for more heterogeneous samples is less obvious. Static light scattering methods could make lignin particle size analysis more rapid and automated, thus enhancing lignin valorization, but should be applied carefully to avoid systematic errors.